Total reconstruction of the nose in settings where resources are limited. Issue 10 (December 2015) - Rodgers, W.; Lloyd, T.; Fourie, L.; Nishikawa, H.; Kuoraite, D.; Dunaway, D.; Bulstrode, N.
Abstract: We describe a series of 8 patients who had total reconstruction of the nose during 4 separate missions to Ethiopia. The aetiology was noma (n = 3), assault (n = 2), acid burn (n = 1), squamous cell carcinoma (n = 1), and a sequela of meningococcal septicaemia (n = 1). Reconstruction was with forehead flaps when adequate tissue was available (n=6) and with radial forearm flaps when it was not (n=2). Some reconstructive approaches require procedures to be done in stages, and in settings where resources are limited, difficulties with the continuity of care and provision for the management of complications, must be overcome.